Social support, social maladjustment, and psychological wellbeing as determinants of psychopathic deviance among civil servants in Akure, Nigeria (2011)
The influence of social support, social maladjustment and psychological wellbeing on psychopathic deviance (PD) among civil servants in Akure, Nigeria was investigated. The survey adopted a cross-sectional design including 194 male and 153 female participants with a mean age of 33.97 years, selected using multi-stage sampling. Data was collected using an 89-item structured-questionnaire. Four hypotheses were tested of which two were confirmed. Social maladjustment (F [1, 339]= 120.49; p= .001), and general health (F [1, 339] = 41.83; p= .001); as well as a combination of social support, social maladjustment, and general health (F [1, 3092] = 52.47; p= .001) significantly influenced PD; General health (GH) predicted PD (R2=.51, F [3,343] = 90.21; P<.0l). There were significant differences between participants high and low social maladjustment (t [345] = -9.52; P> 0.00), and GH (t [345] = -9.08; P = 0.00) on PD, but not between participants with high and low social support (t [345] = -0.23; P = 0.82). This shows that the psychological factors determine PD among civil servants. Prospective employers should investigate these variables among civil service applicants, while psychological interventions would be imperative for secondary PD prevention in having mentally-healthy civil servants.